Perineural Invasion Is a Significant Indicator of High Malignant Degree and Poor Prognosis in Esophageal Cancer: A Systematic Review and Meta-Analysis - Bai, Liuyang; Yan, Liangying; Guo, Yaping; He, Luyun; Sun, Zhiyan; Cao, Wenbo; Lu, Jing; Mo, Saijun (Frontiers in Oncology, 2022)
Abstract Background: Perineural invasion (PNI) is a malignant metastatic mode of tumors and has been reported in many tumors including esophageal cancer (EC). However, the role of PNI in EC has been reported differently. This systematic review and meta-analysis aims to focus on the role of PNI in EC. Methods: Nine databases of CNKI, VIP, Wanfang, Scopus, Wiley, ISI, PubMed and EBSCO are used for literature search. The association of PNI with gender, pathological stages of T and N (pT and pN), lymphovascular invasion (LVI), lymph node metastasis, 5-year overall survival (OS) and 5-year disease-free survival (DFS) was examined in the meta-analysis by Revman5.0 Software. The pooled OR/HR and 95% CI were used to assess the risk and prognostic value. Results: 69 published studies were screened for analysis of PNI in EC. The incidence of PNI in esophageal squamous carcinoma (ESCC) and esophageal adenocarcinoma (EAC) was different, but not statistically significant (P＞0.05). The PNI positive patients had significant higher risk of pT stage (OR=3.85, 95%CI=2.45-6.05, P<0.00001), pN stage (OR=1.86, 95%CI=1.52-2.28, P<0.00001), LVI (OR=2.44, 95%CI=1.55-3.85, P=0.0001) and lymph node metastasis (OR=2.87, 95%CI=1.56-5.29, P=0.0007), respectively. Furthermore, the cumulative analysis revealed a significant correlation between PNI and poor OS (HR=1.37, 95%CI=1.24-1.51, P<0.0001), as well as poor DFS (HR=1.55, 95% CI=1.38-1.74, P<0.0001), respectively. Conclusion: PNI occurrence is significantly related to tumor stage, lymphovascular invasion, lymph node metastasis, OS, and DFS. These results indicate that PNI can serve as an indicator of high malignant degree and poor prognosis in EC.